The Effect of Financial Attitude and Financial Knowledge on Financial Management Behavior with Self-Control as an Intervening Variable on Management Students of The First Class of Royal University - Astuti, Bela (Eastasouth Institute, 2025)
This study was conducted to determine the effect of Financial Attitude (X1), Financial Knowledge (X2), on Financial Management Behavior (Y) with Self-Control as an Intervening Variable (Z) with the object of research being Management Students of Batch 1 of Royal University. The population in this study was 67 respondents, then a saturated sampling technique was used so that the sample took all the population into a sample of 67 respondents. Data analysis used the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method through SmartPLS 4 software. The test results showed that Financial Attitude had a positive and significant effect on Financial Management Behavior, Financial Attitude had a positive and significant effect on Self-Control, Financial Knowledge had a positive and significant effect on Financial Management Behavior, Financial Knowledge had a positive and significant effect on Self-Control, Financial Attitude had a positive and significant effect on financial management behavior through self-control, and Financial Knowledge had a positive and significant effect on financial management behavior through self-control.